CLINICAL ASSISTANCE ALGORITHM FOR THE DENTAL IMPLANT CANDIDATE - Florin Rosu; Doriana Agop Forna; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2017)
The anesthesia of the dental implant candidate is challenging, both from the point of view of the patient's comfort and of the dentist's (the patient needs to sleep, not to feel pain, to breathe efficiently, to have the deglutition reflex and to execute simple orders given by the implantologist). A lot of 120 patients was used for this study - candidates for dental implant who were subject to anesthesia. The patients were divided into two lots: Lot A - 20 patients sedated using the inhalo-sedation method and Lot B - 100 patients who were administered intravenous general anesthesia. When the surgical maneuvers were initiated, the effect of Midazolam was augmented with 1 g of Algocalmin (which is repeated every 1 and ½ hours - in case of interventions that exceed 2 hours). As a continuation dose, Midazolam was administered in a concentration of 0.1 mg/kg/h, with a total dose of 3.5 / 7.5 mg (usually, no doses in excess of 5 mg are necessary). However, the patients react differently to Midazolam, which is why the dose needs to be adjusted depending on the metabolic capacity of each patient. In case of patients over 60, 1 mg is administered initially (usually no doses in excess of 3.5 mg are necessary). The choice of sedation and general anesthesia belongs exclusively to the ATI doctor who, following a rigorous pre-anesthetic consult, will decide upon the most suitable and risk-free method that needs to be used during the surgical intervention.